Pelatihan pengolahan minyak kelapa secara fermentasi bagi masyarakat di Kampung Mansaburi: Fermentation-based coconut oil processing training for the community of Mansaburi Village - Yuminarti, Umi; Widati , Agatha W.; Wambrauw , Ludia Th.; Imbiri , Soleman; Ramadhani , Fika N. (Fakultas Peternakan Universitas Papua, 2025)
ABSTRACT Mansaburi Village is known for its abundant coconut production, which has not been optimally utilized due to limited technical skills and inadequate processing technology. This community service program aims to enhance the capacity of Mansaburi Village residents in processing coconuts into Virgin Coconut Oil (VCO) using a natural, hygienic, and economically valuable fermentation method. The activities were carried out using a participatory approach, including community outreach, technical training, and hands-on practice. The results of the program showed a high level of enthusiasm from the community throughout the implementation, along with a significant improvement in their knowledge and skills in VCO production. Additionally, several participants took the initiative to form small business groups. This program has had a positive impact on the community’s economic self-reliance and has opened up opportunities for the development of local coconut-based products. Keywords: Coconut; Fermentation; Local Product; Virgin Coconut Oil ABSTRAK Kampung Mansaburi merupakan kampung yang memiliki hasil kelapa berlimpah dan belum optimal dalam pemanfaatan kelapa tersebut akibat minimnya keterampilan teknis dan terbatasnya teknologi pengolahan. Program pengabdian masyarakat ini bertujuan untuk meningkatkan kapasitas masyarakat Kampung Mansaburi dalam mengolah kelapa menjadi Virgin Coconut Oil (VCO) melalui metode fermentasi yang alami, higienis, dan bernilai ekonomi tinggi. Kegiatan dilaksanakan dengan pendekatan partisipatif, meliputi sosialisasi, pelatihan teknis dan praktik langsung. Hasil program menunjukkan antusiasme masyarakat sangat tinggi selama kegiatan pengabdian serta adanya peningkatan signifikan dalam pengetahuan dan keterampilan masyarakat dalam proses produksi VCO, serta munculnya inisiatif warga untuk membentuk kelompok usaha kecil. Program ini memberikan dampak positif terhadap kemandirian ekonomi masyarakat dan membuka peluang pengembangan produk lokal berbasis kelapa. Kata kunci: Kelapa; Fermentasi; Produk Lokal; Virgin Coconut Oil